Comparison Between Mercury and Liquid Crystal Forehead Thermometers for Measurment of Body Temperature - Rahman, Nilufar; Kasem, Fouzia Binte; Islam, Md Reazul; Islam, Md Rafiqul; Sultana, Rezina; Matin, Abdul (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Body temperature is a measure of the body's ability to generate and get rid of heat. For recording of body temperature several different types of thermometers are available, such as mercury thermometers, digital thermometer, liquid crystal forehead thermometer, and infrared tympanic thermometer are used. The accuracy of the device is to record and grade temperature is uncertain. Objective: The study was carried out the recordings of normal body temperature using liquid crystal forehead thermometer and compare with gold standard oral mercury thermometer. Methodology: Simultaneous recording were made using the two devise in randomly enrolled 150 apparently healthy medical student eighteen (18) to twenty (20) years age of either sex. Written & verbal consent was taken from the students without any coercion. Oraltemperature was recorded with Chinese made mercury thermometer and the forehead temperature was recorded using liquid crystal (Boots, UK) thermometer. Results: No statistical significant difference existed between the recordings of two devices. The mean difference was 0.8 degree. Liquid crystal forehead thermometer recorded higher temperatures. Both the devices recorded temperature within normal range. Conclusions: Sensitivity of liquid-crystal thermometer to detect body temperature is comparable with that of mercury thermometer. It is a good device for home use but health providers should not use it. Mercury thermometer remains the gold standard. DOI: http://dx.doi.org/10.3329/jssmc.v4i2.14421 J Shaheed Suhrawardy Med Coll, 2012;4(2):60-61